2014
DOI: 10.1016/j.bcp.2014.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian flavin-containing monooxygenase (FMO) as a source of hydrogen peroxide

Abstract: Flavin-containing monooxygenase (FMO) oxygenates drugs/xenobiotics containing a soft nucleophile through a C4a hydroperoxy-FAD intermediate. Human FMOs 1, 2 and 3, expressed in Sf9 insect microsomes, released 30–50% of O2 consumed as H2O2 upon addition of NADPH. Addition of substrate had little effect on H2O2 production. Two common FMO2 (the major isoform in the lung) genetic polymorphisms, S195L and N413K, were examined for generation of H2O2. FMO2 S195L exhibited higher “leakage”, producing much greater amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 42 publications
5
79
0
Order By: Relevance
“…Tynes et al [34] found hydrogen peroxide produced by the purified rabbit lung FMO (FMO2) at up to 41% of the total NADPH oxidized. More recently Siddens et al [35] published data on three human FMOs, where the percentage of molecular oxygen consumed that appeared as H 2 O 2 varied between 30 and 50% at a rate of 0.5-2.5 nmol/min/nmol FMO. However, all these uncoupling data are for mammalian FMO enzymes and to our knowledge no such data has been reported for the bacterial BVMO enzymes.…”
Section: Measurement Of the C4a-(hydro)peroxyflavin Intermediatementioning
confidence: 99%
“…Tynes et al [34] found hydrogen peroxide produced by the purified rabbit lung FMO (FMO2) at up to 41% of the total NADPH oxidized. More recently Siddens et al [35] published data on three human FMOs, where the percentage of molecular oxygen consumed that appeared as H 2 O 2 varied between 30 and 50% at a rate of 0.5-2.5 nmol/min/nmol FMO. However, all these uncoupling data are for mammalian FMO enzymes and to our knowledge no such data has been reported for the bacterial BVMO enzymes.…”
Section: Measurement Of the C4a-(hydro)peroxyflavin Intermediatementioning
confidence: 99%
“…1). Uncoupling has been observed in both the presence and the absence of substrate in vitro, resulting in "leakage" of hydrogen peroxide, and less frequently, superoxide (7). FMOs are notable for their "cocked and loaded" mechanism where they bind NAD(P)H and reduce FAD in the absence of substrate, creating an unusually stable C4a-hydroperoxyflavin ready to oxidize any substrate that accesses the active site (6).…”
Section: Catalytic Cyclementioning
confidence: 99%
“…The rate-limiting step of FMOs is thought to be the release of either H 2 O or NADP ϩ . The significance of FMOs' reaction kinetics, reactive oxygen species leakage, and effects on cellular NAD(P)H is not known (7,8).…”
Section: Catalytic Cyclementioning
confidence: 99%
“…The amine oxidases are members of the FAD monooxygenase (FMO) class, which are important sources of H 2 O 2 within the lung and play a critical role in xenobiotic metabolism (Francois et al, 2009;Siddens et al, 2014;Zhang et al, 2006). The FMOs of lung are distinctly different from liver, with FMO2 being the predominant form in adult lung; and there appears to be a distinct developmental aspect to their expression Hines, 2006).…”
Section: Amine Oxidationmentioning
confidence: 98%